Managing the shopping centre as a consumption site : creating appealing environments for visitors : some Australian and New Zealand examples : a thesis in presented [sic] in partial fulfilment for the requirements for the degree of Doctor of Philosophy in Geography at Massey University - Bowler, Susan Mary (Massey University, 1995)
The position occupied by retailing within the production - consumption debate is the subject of dispute. As neither sphere can be fully analysed in isolation such argument may be somewhat irrelevant. The need to conceptualise the two spheres together, therefore, has informed this research on the created environments of shopping centres. Planned and managed shopping centres are a ubiquitous part of the built environment in 'advanced capitalist' nations. There has been a tendency, however, for researchers to focus upon exceptional centres rather than everyday examples of this particular consumption site. They have concentrated upon how shopping centre environments appear to be created and the appeal researchers assume they may have for an observer. My research for this thesis, however, has been concerned with how managers create shopping centre environments and how they are designed so as to appeal to their centres' perceived markets. This was done by conducting semi - structured interviews with a number of centre managers in Australia and New Zealand . The unified ownership and management structure of shopping centres makes it easier for their created environ ments to be controlled. Shopping centre researchers and those who have attempted to read the built environment as if it were a text have tended to assume that the architectural styles used will reflect dominant ideologies and that they are powerless to interpret or alter them in any other than the manner intended by the designers, developers and owners. Many of the managers recognised, however, that shoppers cannot be forced to visit nor can they be made to purchase. Research was therefore commissioned by management as a way of gaining socio - economic information on the individuals in their catchments , their 'needs' and desires. Selecting tenants which would appeal to their markets and arranging them in a manner which reflected the way people liked to shop was thought to be paramount to the success or otherwise of a centre. Some managers, for example, claimed that there was a difference between 'doing' the shopping (which is a chore) and 'going' shopping (which is enjoyable ) and that this needed to be kept in mind when they positioned retailers within their centres. Consumption does not only involve the purchase of commodities for their use and/or sign value but is also concerned with experience. Managers attempted to provide their shoppers with an enjoyable experience when they visited their centres by, for example, the creation of an appealing ambience and by either suggesting or insisting, respectively, that the common areas and leased spaces be regularly refurbished.
Keywords: Shopping environments; Shopping centre management; Fields of Research::370000 Studies in Human Society::370400 Human Geography